Effectiveness of mussels (Mytella falcata) in malnourished children's recovery living in the slums in Maceió, Alagoas - Larissa Tenório Andrade Correia; Gabriela Rossiter Stux Veiga; Táscya Morganna de Morais Santos; Cristianni Gusmão Cavalcante; Ana Lydia Sawaya; Telma Maria de Menezes Toledo Florêncio
Abstract Objectives: to assess the efficacy of mussels (Mytella falcata) in malnourished children's recovery. Methods: 64 chronically malnourished children were accompanied for 12 months and attended at the Centro Recuperação e Educação Nutricional (Recovery Center and Educational Nutrition). The children were paired by age and malnutrition level forming three groups, which they received a balanced diet for nutritional recovery differing only on protein source. The group was offered (1) preparation of red meat, group (2) preparation of mussels and group (3) preparation of mussels in coconut milk. Results: the anthropometric assessment revealed that the children obtained a mean increase in the Z score in A-I indice of 0.70 for the group who red meat, 0.62 for the group who had mussels and 0.57 the group who had mussels cooked in coconut milk (p<0,05). An observation was made on a reduction in the prevalence of anemia with 22,8% (p=0,002), 27.8% (p=0.,007) and 42.4% (p 0.001) in groups 1, 2 and 3, respectively. Conclusion: the preparation of mussels cooked in or not in coconut milk can be an effective substitution for meat in combating child malnutrition and anemia and may be included in the children's institutions menus and in the programs that aim for children's nutritional recovery.